Unusual causes of upper gastrointestinal bleeding - De zoysa, M.I.M.; Dharmawardhane, K.A.A.S.; Seneviratne, S.A.; Ramanayake, I.T.; De Silva, W.D.D.; Sairam, K. (My University, 2012)
Common causes of upper gastrointestinal (UGI) bleeding are oesophageal varices, gastric erosions and peptic ulcers. However, few patients may present with UGI bleeding due to other rare causes, and we report a series of such patients who presented with haematemesis or haematochezia due to uncommon pathology.